2017
DOI: 10.1108/jima-01-2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

A crystallized exposition on Indian Muslims’ attitude and consciousness towards halal

Abstract: Purpose This study aims to investigate the attitude and consciousness of Indian Muslims toward halal and also to indicate the alertness of Muslim students about halal in their daily life. Design/methodology/approach A total of 500 respondents were selected for the study from the State of Andhra Pradesh in India, by stratified random sampling method; of which 300 were general Muslims and 200 were Muslim students. Self-administrated questionnaire and personal interviews were administered to garner the data, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 10 publications
0
16
0
1
Order By: Relevance
“…The Muslim minority, with a population exceeding over 170 million, constitutes about 14.6 percent of India's total population. The population is expected to grow to 236 million by 2030, and the share is likely to be 18%-19% of India's population (Potluri et al 2017). By 2050, India's Muslim population is projected to become the largest in the world (Kurpad 2016).…”
Section: Research Theme 3: Islamic Finance Marketing In Emerging Counmentioning
confidence: 99%
“…The Muslim minority, with a population exceeding over 170 million, constitutes about 14.6 percent of India's total population. The population is expected to grow to 236 million by 2030, and the share is likely to be 18%-19% of India's population (Potluri et al 2017). By 2050, India's Muslim population is projected to become the largest in the world (Kurpad 2016).…”
Section: Research Theme 3: Islamic Finance Marketing In Emerging Counmentioning
confidence: 99%
“…The study found that taste and nutrition is the top of priority in consuming the chicken-based food, while halal becomes the second priority. Another research performed by Potluri et al (2017) who studied about Indian Muslims' attitude and consciousness toward halal product. The study found that the respondents do not have proper exposure to halal, believe that the halal concept is very significant to Muslim consumers and the lack of awareness of the factual meaning of halal.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have examined and shown the positive influence of halal awareness and its implications on behavioral intention [1,4,5]. Conversely, some studies show that halal awareness does not influence behavioral intention [6]. Therefore, this study resolves the gap regarding inconsistent findings on halal awareness on behavioral intention.…”
Section: Introductionmentioning
confidence: 69%